Age trends of genetic parameters, early selection and family by site interactions for growth traits in Larix kaempferi open-pollinated families. Issue 1 (December 2016) - Diao, Shu; Hou, Yimei; Xie, Yunhui; Sun, Xiaomei
Background Japanese larch (Larix kaempferi ) as a successful exotic species has become one of the most important economic and ecological conifers in China. In order to broaden the genetic resource ofLarix kaempferi, an effort was made in 1996 to introduce 128 families from seven seed orchards in Japan, with which to establish two progeny trials in climatically different environments. The experiment was aimed to determine the strategy of early selection, particularly important for long-rotated Japanese larch, and the optimal breeding program for specific environments. Result Growth trajectories revealed different growth performances of stem height (HGT) and diameter at breast height (DBH) in two different environments, Hubei and Liaoning. In both sites, there were marked variabilities in HGT, DBH and volume (VOL) among families at each year. The trends of individual and family heritability and age-age correlations were found to follow a certain dynamic pattern. Based on these trends, the optimum selection age was determined at four years for HGT and five years for DBH in Hubei and Liaoning. Genetic gains for VOL were 34.4 and 6.04 % in Hubei and Liaoning respectively when selection ratio was 10 % at age 16. Type-B correlations were less than 0.67 and rank correlations of breeding value were less than 0.4 for HGT, DBH and VOL between the two sites, revealing that there exist pronounced family-by-site interactions for the growth traits ofLarix kaempferi . Conclusions Early selection forLarix kaempferi is an effective strategy to overcome its long rotation age. In early selection, dual growth trait selection is more effective than single one. Regionalization deployment should be considered inLarix. kaempferi breeding program based on different environmental factors.